AN ANALYSIS OF STUDENT’S PROBLEMS IN COMPREHENDING DESCRIPTIVE PARAGRAPHS AT SMPN 6 KERINCI THE ACADEMIC YEAR 2017/2018 - Putra, Reko Hary (Qawwam : The Leader's Writing, 2023)
Based on the problems above, the study is intended to know about the student's problem in comprehending descriptive paragraphs. In this research, the researcher used a descriptive paragraph. It consisted of 10 multiple-choice questions and 5 essay questions. The purposes of this research were to know the student's problems in comprehending descriptive paragraphs and to know the cause of factors in the student's problems in comprehending descriptive paragraphs. The researcher used qualitative descriptive methods and the technique to collect the data are tests and interviews. The participant of this research is the class IX A students of SMPN Kerinci. The result of this research from 20 that there were 2,91% of students did problems identifying the main idea, 5,83% of students made mistakes identifying function, 8,74% of students did cannot identifying purposes, 37,87% students did cannot identifying specific items in multiple choice questions and 31, 06% the students mistake identifying the specific item in the essay question, and the last problems the students did not identify major tenses used in the paragraph there were 13,59% students. Then the interview results in the research find the cause of factors in students' problems in comprehending paragraphs from 20 students’ there are 80% of students get problems in comprehending descriptive paragraphs caused by some factor. First, the students lack vocabulary by 30%. Second 20 % of the students difficulties translate the paragraph. The third situation in the class influences 15% of students. Fourth 10% of the students’ experience had a low interest in learning. Finally, the students needed media in learning 5%.